Pengaruh Label Halal dan Citra Merek Terhadap Keputusan Pembelian Produk Kosmetik Somethinc di Kota Mataram - Rahayu, Baiq Tris Saptianing; Sudiartha Athar, Handry (Postgraduate, University of Mataram, 2025)
Cosmetics are a series of facial treatments used by women. Customer choice is strongly influenced by individual brand choice. One of the things that can influence consumer purchasing decisions is the influence of the halal label and brand image. This study aims to determine the effect of halal labels and brand image on purchasing decisions. This research method is an associative quantitative method with a sample of 100 respondents. The sample in this study used nonprobability sampling techniques. The types of data used in this study are primary and secondary. Primary data in this study are responses or answers to respondents' questionnaires. Meanwhile, the secondary data used in this study are references obtained through literature studies. Researchers used a questionnaire as a tool to obtain data on the three variables in this study. In the data analysis procedure, validity and reliability tests were carried out. At this stage, the data is processed so that it can be concluded that the data is correct to answer the problems that arise in the study. Furthermore, the classical assumption test, multiple linear regression analysis, and model test were carried out. This study concludes that the halal label and brand image have a positive and significant effect on purchasing decisions for some products in Mataram City.